Levantamiento y diseño de procesos en el Gobierno Autónomo Descentralizado Parroquial Rural de Cutuglagua, año 2014. - Guerrón Pita, Martha Patricia (2014)
A survey process was conducted in the Autonomous Government Decentralization Parish Rural Cutuglahua, to comply with this uprising received the support of all servers to collect the necessary information that led to the development of the manual process, note that all processes are approved by servers, reflect the current status of the institution and are a practical tool for everyday work. This thesis has three chapters detailed below: Details the institution, the main problems they have and the formulation of objectives and hypotheses. Describe the theoretical framework which served to support the development of the thesis. Regarding methodology, here an analysis of the current situation of the institution was carried out from this based on the theoretical framework reference proceeded to perform lifting processes, they were validated and captured in a manual as a guide to all servers.